Unmasking the challenges in ideological world and political education in China: a thematic review - Mat Rashid, Abdullah; Sha, Ouyang; Hassan, Aminuddin; How, Shwu Pyng; Zhang, Wei; Xu, Jian (Elsevier, 2024)
China's distinctive educational approach, particularly its emphasis on ideological and political education, has garnered considerable academic attention for its impact on shaping individual values, fostering citizenship, and maintaining social stability. Despite the Chinese government's prioritization of ideological and political education, academic research in this field appears constrained, with existing studies predominantly focusing on normative and descriptive aspects. Normative research delineates how ideological and political education should be executed, while descriptive research illustrates its practical implementation. The effectiveness of these approaches is significantly diminished if they are not adequately interconnected—when only the current reality is explained without providing tools for improvement or when prescribed steps for improvement lack a basis in specific contexts. This paper conducts a comprehensive review of research on ideological and political education using ATLAS. ti 9 for thematic analysis. The review aims to unveil the intricate landscape of current research in China and address key questions: What are the primary trends in the literature on ideological and political education between 2021 and July 2023? What challenges does ideological and political education face? Through a direct exploration of these issues, this paper seeks to optimize the ideological and political education system, elevate its adaptability and effectiveness, and open avenues for research, fostering a more dynamic, inclusive, and resilient development of ideological and political education.